PENGARUH CAMPURAN LIMBAH TUNGGAK KAYU TUMIH (Combretocarpus rotundatus (Miq) Danser) DAN LIMBAH KAYU GALAM (Melaleuca cajuputi) TERHADAP KARAKTERISTIK BRIKET ARANG DARI KAYU KHAS LAHAN BASAH DI KALIMANTAN SELATAN - Noor Mirad Sari; Violet Violet; Khairun Nisa; Syamsudin Syamsudin (Lambung Mangkurat University-Indonesia, 2021)
Tumih (Combretocarpus rotundatus (Miq.) Danser) and Galam (Melaleuca cajuputi) are typical vegetation of the wetlands of South Kalimantan. Tumih and galam wood waste can be made into charcoal briquettes which have economic value. The aims of this study were: 1) Analyzing the characteristics of charcoal briquettes, namely: water content, density, ash content, volatile matter content, bound carbon content and calorific value and 2) Knowing the best treatment from a variety of treatments. The design model used was a completely randomized design (CRD) with 4 treatments and 3 replications. The process of making charcoal briquettes at the Forest Products Technology Laboratory. Testing the characteristics of charcoal briquettes was done at the Laboratory of the Research and Industrial Standardization Institute (BARISTAND) Banjarbaru. The results of the analysis of diversity showed that the mixed treatment of tumih wood waste and galam wood waste had a very significant effect on water content, ash content, volatile matter content, bound carbon content and calorific value, but had no significant effect on density. The water content of charcoal briquettes from galam wood waste and tumih wood waste and the combination of a mixture of galam wood waste and tumih wood waste ranged from 6.1133-10.6667 %, the average density value was between 0.5228-0.5897 g/cm3, the average value The average ash content is between 1.3000-2.9300%, the volatile matter content shows an average range of 41.6333-48.4767%, the average value of bound carbon content is 37.9267-50.5400% and the average calorific value ranged from 5084.41 to 6230.59 cal/g. Treatment A3 (25% galam wood waste + 75% tumih wood waste is the best treatment and meets American standards for moisture content and calorific value. Ash content of all treatments are A1. A2, A3 and A4 meet American standards.